Сварка и родственные технологии в медицине - Патон, Б.Е. (Автоматическая сварка, 2008)
Considered are R&D efforts and experien ce of using welding and related technologies in different medical applications: electric welding of soft live tissues to join damaged tissues and recover vital activity of human and animal organs; hyperthermic methods for welding, cutting and treatment of live biological tissues; magnetron sputtering of coatings used to cure cardiovascular diseases; implants, prostheses and surgical instruments of shape memory alloys; bioceramic microplasma coatings for endoprostheses; composite materials produced by using nanotechnologies for targeted transportation of medical preparations in a living organism; and steam-plasma technologies for disposal of medical wastes.